Convergence of mammalian RQC and C-end rule proteolytic pathways via alanine tailing - Thrun, Anna; Garzia, Aitor; Kigoshi-Tansho, Yu; Patil, Pratik Rajendra; Umbaugh, Charles Samuel; Dallinger, Teresa; Liu, Jia; Kreger, Sylvia; Patrizi, Annarita; Cox, Gregory A.; Tuschl, Thomas; Joazeiro, Claudio A. P. (Molecular cell, 2021)
Incompletely synthesized nascent chains obstructing large ribosomal subunits are targeted for degradation by ribosome-associated quality control (RQC). In bacterial RQC, RqcH marks the nascent chains with C-terminal alanine (Ala) tails that are directly recognized by proteasome-like proteases, whereas in eukaryotes, RqcH orthologs (Rqc2/NEMF [nuclear export mediator factor]) assist the Ltn1/Listerin E3 ligase in nascent chain ubiquitylation. Here, we study RQC-mediated proteolytic targeting of ribosome stalling products in mammalian cells. We show that mammalian NEMF has an additional, Listerin-independent proteolytic role, which, as in bacteria, is mediated by tRNA-Ala binding and Ala tailing. However, in mammalian cells Ala tails signal proteolysis indirectly, through a pathway that recognizes C-terminal degrons; we identify the CRL2KLHDC10 E3 ligase complex and the novel C-end rule E3, Pirh2/Rchy1, as bona fide RQC pathway components that directly bind to Ala-tailed ribosome stalling products and target them for degradation. As Listerin mutation causes neurodegeneration in mice, functionally redundant E3s may likewise be implicated in molecular mechanisms of neurodegeneration.